2017
DOI: 10.22159/ajpcr.2017.v10i8.14233
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Characterization, and in Vitro Evaluation of Probiotic Properties of Lactobacillus Strains

Abstract: Objective: The aim of the present investigation was to isolate and identify Lactobacillus strains from dairy and cattle dung samples. Potent isolates were selected for screening by antimicrobial activity; selected lactobacilli were further tested for probiotic properties and adhesive attributes.Methods: Lactobacilli were isolated aseptically on specific de man, rogosa and sharpe medium from dairy and cattle dung samples. Isolates were identified by Gram-staining, motility, catalase, endospore, and carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…For example, BMS 1.1 experienced a 37% decrease indicating lower resistance to acid. This result for BMA 3.3 is even higher than the lactic acid bacteria isolated from milk and cattle dung samples by Jain et al [13], which is regarded as a potential probiotic because it can survive at pH 2 (56.93-80.88%) and pH 3 (61.44-81.25%). While the lactobacillus investigated by Singh et al [17] showed a tolerance to acid at pH 2 (46.47-79.74%).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…For example, BMS 1.1 experienced a 37% decrease indicating lower resistance to acid. This result for BMA 3.3 is even higher than the lactic acid bacteria isolated from milk and cattle dung samples by Jain et al [13], which is regarded as a potential probiotic because it can survive at pH 2 (56.93-80.88%) and pH 3 (61.44-81.25%). While the lactobacillus investigated by Singh et al [17] showed a tolerance to acid at pH 2 (46.47-79.74%).…”
Section: Resultsmentioning
confidence: 66%
“…Overall, BMA 3.3 shows the most promising antibacterial properties against both common pathogens. The antibacterial activity of BMA 3.3 isolates against S. aureus ATCC 25923 and E. coli O157:H7 was lower than that of Lactobacillus fermentum isolated from buffalo milk by Jain et al [13], which had higher antibacterial activity against S. aureus (20.34 ± 0.02 mm). However, the strain does show a significant protective effect against both E. coli and S. aureus.…”
Section: Antibacterial Activity Against Pathogensmentioning
confidence: 70%
See 1 more Smart Citation
“…These guidelines state that safety and functionality properties like resistance to bile toxicity, gastric acidity, and antibiotic resistance, adhesion to intestinal cell lines, antimicrobial activity, cholesterollowering potential, and immunomodulation potential are extremely important and should be investigated using dependable in vitro screening methods. In the current investigation, isolated lactobacillus from commercial probiotics was assessed for its probiotic qualities using in vitro assay techniques (Neha Jain et al, 2017) [20] . When L. Vannamei tanks' water quality was taken into account, the pH ranged from 8.2 to 8.9 in probiotic-treated ponds whereas it stayed below 8 in controls (Sreenivasulu et al, 2016) [29] .…”
Section: Resultsmentioning
confidence: 99%
“…The yield of palm sugar isolate was even higher than that of Lactobacillus rhamnosus isolated from buffalo milk from Karnataka, India, which had a viability of 30% at pH 3 for 3 hours (Shafakatullah and Chandra 2014). Lactic acid bacteria isolated from milk and cow dung samples by Jain et al (2017) can survive at pH 3 (71.05-84.61 %).…”
Section: Resistance Of Lactic Acid Bacteria To Acidic Conditionsmentioning
confidence: 99%